(untitled) (Architecture Image Studies, 2026)
This research aims to demonstrate the effect of the method adopted by the architectural designer to employ the reference in generating the architectural product, which may be an imitative product or an innovative product. The field of study focuses on the references and design methods that influence the nature of architectural production and imitation and innovation in architecture. In the midst of this confusion in the design output of contemporary architecture, the problem of this research emerges in exploring the references that generate imitational outputs and the references that generate innovative outputs in architecture. To achieve this, the study has set two objectives: The first is what is the reference for generating the design concept? The second is what is the method that the designer relies on towards the reference to generate the design concept? The study adopted the qualitative analysis approach of building shapes to achieve the first objective and the qualitative inferential approach using the pre-structured interview method with a selected number of architectural experts to verify the second objective. The results of the study were summarized as follows: The most widely used methods for generating traditional ideas for architectural production is the imitation method, which relies on imitate and replicating references from within the field of architecture, while the metaphor method is used to generate innovative ideas for architectural production, which relies on abstracting and modifying references from outside the field of architecture.